ARXETIP HÁM MIFOLOGEMA TÚSINIKLERINDEGI PARQLAR - Kdirbaeva, G.K. (SCIENCE and SOCIETY, 2025)
The article examines the theoretical foundations and methodological approaches to distinguishing these concepts in linguistics, literary studies, and cultural studies. Special attention is given to the interaction between archetypes and mythologemes in literary works. The findings demonstrate that while archetypes and mythologemes are interconnected, they serve distinct functions: archetypes provide deep universality to images, whereas mythologemes shape their cultural and historical specificity. These insights contribute to a more precise understanding of these categories and may be valuable for further research in literary analysis, intercultural communication, and translation studies.